BANKRUPTCY PREDICTION ANALYSIS OF PT GARUDA INDONESIA TBK (2018-2023) USING THE FULMER MODEL (H-SCORE) - Mardiana; Muhammad Fauzan; Lilis Karlina; Syafrinadina, Syafrinadina (Indragiri Research Center (ingreat), 2024)
The COVID-19 pandemic has had a very significant economic impact, with millions of people losing jobs and income, especially in the air transportation (aviation) sector. One of the leading aviation companies in Indonesia that has been affected by the COVID-19 pandemic is PT Garuda Indonesia Tbk. The aim of this research is to evaluate the risk of company bankruptcy using the Fulmer Model (H-Score) with a pre-pandemic (2018-2019), pandemic (2020-2021), and post-pandemic perspective.pandemic (2022-2023). The research method used is a quantitative descriptive method with secondary data sources. The data collection techniques used are literature study, online data search, and documentation. The research results show that there is a significant risk of bankruptcy at PT Garuda Indonesia Tbk during the 2018-2023 period. The risk of bankruptcy increases during the pandemic period, with the risk peaking at the start of the post-pandemic period. The risk of bankruptcy in the post-pandemic period is higher compared to the pre-pandemic period. This indicates that PT Garuda Indonesia Tbk is facing high financial vulnerability, especially during and after the COVID-19 pandemic.